Correlation between Adiponectin and Triglyceride Levels in Pregnancy with and without Gestational Diabetes Mellitus - I Nyoman Gde Sudana; Windarwati Windarwati; Budi Mulyono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Gestational Diabetes Mellitus (GDM) is glucose intolerance during pregnancy. Adiponectin causes a decrease in glucose transporter 4 translocation, which reduces glucose uptake due to downstream insulin signal delivery and decreases non-esterified fatty acids so that triglyceride synthesis decreases in pregnancy. This study was conducted to determine the relationship between adiponectin and triglyceride levels in pregnancy, especially in a pregnant female with and without gestational diabetes mellitus. This observational cross-sectional study was conducted by measuring the levels of adiponectin and triglycerides in pregnancy, with and without gestational diabetes mellitus. Researchers proved by analyzing 75 subjects, 24-28 weeks pregnant females who were examined at the primary health center and Dr. Sardjito Hospital, Yogyakarta. Adiponectin levels have a moderate negative correlation with triglycerides in pregnant females (r= -0.420 and p=0.002), a strong negative correlation with GDM (r = -0.680 and p=0.001), and moderate negative correlation (r= -0.455, and p=0.022) with those without GDM. Based on this research can be concluded that adiponectin has a moderate negative correlation with triglycerides in pregnancy, a strong negative correlation in pregnant females with gestational diabetes mellitus, and a moderate negative correlation in those without gestational diabetes.